Síntese de pigmentos zeolíticos a partir de zeólita A derivada de rejeito de caulim da Amazônia - MENEZES, Raquel Aranha de (Universidade Federal do Pará, 2015)
Ultramarine pigments were successful synthesized from zeolite A obtained from kaolin waste. This waste has been used as an excellent source of silicon and aluminum for zeolite synthesis because of its high kaolinite concentrations and low contents of other accessory minerals. The cost is naturally less than the industrialized product. The zeolite NaA derived from kaolin waste presents characteristics favorable for synthesis ultramarine pigments, sulfur species can be inserted inside the zeolite voids, which act as chromophores, and should provide some protection against oxidation and avoids high levels of toxic gases during reaction. Zeolite A was mixed with Sulfur and Sodium Carbonate in different proportions in order to check the influence of this variation in color and shade of pigments. Further calcined for 5 hs@500º C. They were characterized by XRD, XRF and, Raman in addition to visual classification by color and shade. These products show colors from blue to green at different shades, both influenced by the amount of additives, cooling rate after calcination and by particle size. Thus, a different quantity of the same additives in the same zeolitic matrix provides an increase in the color intensity, cooling rate after calcination and particle size induces the color change. X-ray diffraction patterns showed that the structure of zeolite NaA is not change in sodalite type as normally found in the literature. Raman spectroscopy identified sulfur species responsible for color in zeolitic pigments. S6 2- is yellow and S3- is blue and the mixture both is green, majority color in this work. Utilization the kaolin waste in the production of zeolitic pigments is a good proposal for sustainable production.